Influence of diameter of the cored wires on abrasive wear resistance of arc sprayed coatings. Issue 1 (May 2021) - Pokhmurska, H; Student, M; Paczkowski, G; Holovchuk, M; Chumalo, H; Hvozdetskyi, V; Schuberth, S
Abstract: To obtain wear-resistant coatings, the cored wires (CW) with a diameter of 1.6…1.8 mm as electrode materials are mainly used. Using the large-diameter CW enable significantly increase the filling of their shells with powder charges and, as a consequence, to essentially raise the content of alloying elements in the coating structure. The model cored wires of two basic alloying systems Fe – Cr – C and Fe – Cr – B with a diameter of 1.6 and 2.4 mm used for spraying. Three types of the cored wires (namely 50CrNi2B5MnSi, 250Cr21WVMnSi, 50Cr6Mn2MoSi) used in this study. It is found that more oxide phase (40…100 %) was in coatings formed with CW with a diameter of 2.4 mm compared with coatings formed with CW with a diameter of 1.6 mm with lower filling. It is established that the abrasive and gas-abrasive wear resistance of coatings with 250Cr21WVMnSi CW decreased, and with 50CrNi2B5MnSi CW increased due to the increase in the thickness of the lamellae in their structure with the use of CW of larger diameter. It was found that the higher the coefficient of microheterogeneity and chromium content in the lamellae, the higher the corrosion resistance of coatings.